1972
DOI: 10.1111/j.1399-3054.1972.tb03577.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Potassium on the Transpiration Rate and Stomatal Opening in Triticum aestivum andPisum sativum

Abstract: The investigation concerns the influence of potassium on the transpiration rate of Triticum aestivum and Pisum sativum grown in nutrient solutions. Plants with high amounts of potassium were found to have the lowest transpiration rates. Shoot/root ratio, stomatal frequency, and stomatal aperture were correlated with the potassium concentration in the leaves. In Triticum no correlations with leaf concentration of Na were evident.Short term experiments were carried out in order to investigate the effects on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

1973
1973
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 13 publications
1
24
0
2
Order By: Relevance
“…Our results showed that, in olive and sunflower grown in similar controlled conditions, moderate potassium starvation inhibited water-stress-induced stomatal closure. Similar findings have been reported by other authors for sugar cane (Sudama et al, 1998), wheat and pea (Brag, 1972) and, more recently, the 'Chemlali de Sfax' olive cultivar Figure 6. Effect of water availability in the growth medium (irrigation vs. drought) and K + concentration in irrigation water (low K vs. normal K) on stomatal conductance in sunflower leaves.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our results showed that, in olive and sunflower grown in similar controlled conditions, moderate potassium starvation inhibited water-stress-induced stomatal closure. Similar findings have been reported by other authors for sugar cane (Sudama et al, 1998), wheat and pea (Brag, 1972) and, more recently, the 'Chemlali de Sfax' olive cultivar Figure 6. Effect of water availability in the growth medium (irrigation vs. drought) and K + concentration in irrigation water (low K vs. normal K) on stomatal conductance in sunflower leaves.…”
Section: Discussionsupporting
confidence: 87%
“…However, in some of these studies, the potassium deficiency was extreme (Hsiao and Läuchli, 1986). In contrast, other authors suggest that potassium deficiency favours stomatal opening and transpiration in wheat and peas (Brag, 1972), sugar cane (Sudama et al, 1998) and, more recently, in the olive cultivar 'Chemlali de Sfax' (Arquero et al, 2006). It is not yet clear why potassium-deficient plants are more susceptible to dehydration.…”
Section: Introductionmentioning
confidence: 79%
“…During the 1st week the Na concentration increased 5- shown to effect changes in stomatal aperture (3,32) and may have substituted for K directly as the cation taken up by the guard cells. It could also have acted by conserving the supply of leaf K: the addition of Na to K-limited plants might have caused K+ ions to move from the vascular tissue into the mesophyll cells through a cation exchange mechanism, thus releasing K+ ions for specific functions such as stomatal opening.…”
Section: Resultsmentioning
confidence: 99%
“…In alfalfa, a severe K deficiency generally brings on an increase in the stomatal closure (People and Koch, 1979). A low potassium concentration in the nutrient solution produced plants with a high transpiration rate (Brag, 1972). In our work we have used a hydroponic system to study the response of white clover to a stress induced by an osmotic agent.…”
Section: Discussionmentioning
confidence: 99%